The Arrival of Great, Child and Khan Images in Interesting - Bakhtiyorovna, Adizova Nigora (European Journal of Life Safety and Stability (2660-9630), 2022)
In world folklore, we pay special attention to the process of emergence of genres related to folklore, as well as the collection, publication and study of sources reflecting the historical and poetic evolution of children, created to educate children, develop their artistic thinking and aesthetic taste. As a result, it allowed to study the interpretations of the traditions of folklore in Uzbek folklore from the point of view of the evolution of the laws of artistic thinking.